Comparison of uncut Roux-en-Y anastomosis and Billroth-II with Braun anastomosis after distal gastrectomy - Wei, Tianxiao; Wu, Zhouqiao; Chen, Yufan; Li, Yingai; Pang, Fei; Shan, Fei; Li, Ziyu; Ji, Jiafu (Frontiers in Surgery, 2024)
This study aimed to compare the clinical outcomes and patient benefits of uncut Roux-en-Y (URY) anastomosis and Billroth-II with Braun (BB) anastomosis after distal gastrectomy.We retrospectively reviewed the data of patients who underwent URY or BB anastomosis after distal gastrectomy between March 2015 and December 2017. Clinical characteristics, survival data, postoperative recovery data, and long-term outcomes were recorded and compared between the two groups.A total of 231 patients were included, with 167 in the URY group and 64 in the BB group. Kaplan-Meier curves for overall survival showed no differences after propensity score matching (p=0.488). Long-term postoperative quality of life evaluation also showed no significant differences. Compared to the BB group, patients in the URY group had a significantly shorter time to start a liquid diet after propensity score matching (67.6 hours vs 46.5 hours, p=0.003), and a lower occurrence of bile reflux on follow-up gastroscopy (p<0.001).The URY anastomosis appears to be a feasible method for digestive tract reconstruction after distal